Midwifery Care for Pregnant Women with Discomfort of Leucorrhoea in Maternity Hospital: Asuhan Kebidanan pada Ibu Hamil dengan Ketidaknyamanan Keputihan di Rumah Sakit Bersalin - Fitriani, Dwi Ayu; Rinata, Evi (Universitas Muhammadiyah Sidoarjo, 2020)
Pregnancy is the process of fertilization of sperm and ovum that occurs in the fallopian tube. In the third trimester of pregnancy there are various kinds of physiological discomfort, one of which is vaginal discharge. Vaginal discharge is the discharge of mucus from the vagina. Based on data in Indonesia in 2020 there are 25-40% of women who experience vaginal discharge during pregnancy. The purpose of this case study is to determine midwifery care for pregnant women with vaginal discharge discomfort. The case study method used is the observational method. This case study was conducted at PMB Hj. Nafsul Muslichah Magersari Sidoarjo, from 30 December 2019 to 2 February 2020. The process of midwifery care is carried out in a Continuity of Care (CoC) manner and the vaginal discharge experienced by the mother is physiological. And the results obtained from the data collection did not find any gaps with the theory.